2021
DOI: 10.1101/2021.10.25.465749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Desire and Craving ratings vary significantly for healthy alcohol consumers: Differences in semantic interpretation?

Abstract: Craving is a central concept in alcohol, and other substance, research. Beginning in 1955 the World Health Organization outlined a working definition of the term to be used in research and clinical settings. However, the semantic interpretation of craving as a concept is not widely agreed upon. Since the publication of this first craving definition, a handful of studies have been conducted to investigate differences in operational definitions of craving, and have demonstrated a lack of agreement between studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Stress and affect have been widely assessed using EMA methods across a wide array of areas of study including eating behaviors and disorders, stress-related diseases, weight loss and management, and substance abstinence (Engelberg et al, 2005;Fanning et al, 2020;Focht et al, 2002;Goldschmidt et al, 2014;Haedt-Matt & Keel, 2011;Hausenblas et al, 2010;Kanning & Schlicht, 2010;Reichenberger et al, 2018;Shiffman et al, 2008;Smyth et al, 2008;Yoshiuchi et al, 2008). Although alcohol research has traditionally assessed alcohol craving, desire for alcohol has been found to be a more meaningful metric in this non-AUD population (Peterson et al, 2021). Response scales were presented as a horizontal line with vertical rungs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress and affect have been widely assessed using EMA methods across a wide array of areas of study including eating behaviors and disorders, stress-related diseases, weight loss and management, and substance abstinence (Engelberg et al, 2005;Fanning et al, 2020;Focht et al, 2002;Goldschmidt et al, 2014;Haedt-Matt & Keel, 2011;Hausenblas et al, 2010;Kanning & Schlicht, 2010;Reichenberger et al, 2018;Shiffman et al, 2008;Smyth et al, 2008;Yoshiuchi et al, 2008). Although alcohol research has traditionally assessed alcohol craving, desire for alcohol has been found to be a more meaningful metric in this non-AUD population (Peterson et al, 2021). Response scales were presented as a horizontal line with vertical rungs.…”
Section: Methodsmentioning
confidence: 99%
“…Stress and desire for alcohol are also strongly associated with levels of drinking (Breese et al, 2006;Miller et al, 1974;Seo et al, 2011;Uhart & Wand, 2008). Desire for alcohol is used in this study as a more relevant marker of "alcohol craving", as desire has been shown to be a more relevant rating in these non-AUD drinkers than craving (Peterson et al, 2021). Stress reduction is a motivator for alcohol consumption; drinking has been shown to decrease acute ratings of stress, and even the expectancy of alcohol lowers stress in alcohol users (Anthenelii & Grandison, 2012;Cooper et al, 1992;de Wit et al, 2006;Keyes et al, 2012;Pohorecky, 1991).…”
Section: Introductionmentioning
confidence: 99%